A Comparative Study on the Images of Libraries for Library Users and Library and Information Science Experts - Mishima, Yuki; Matsumura, Atsushi (Qualitative and Quantitative Methods in Libraries, 2019)
People have various images of libraries. However, previous studies have not focused on differences in the images of libraries owned by library users and experts in library and information science. Therefore, this study seeks to compare the image of the library as beheld by library users and experts in library and information science, and to examine the difference. The participants are one professor of library and information science in their 50s and three university students in their 20s. For this study, we conducted a survey using Personal Attitude Construct (PAC) analysis (Naito 2002) that combines qualitative research and cluster analysis. There are four procedures: 1. Free association from associative stimulus sentence, 2. Comparison of similarity rating between associative words, 3. Cluster analysis by dissimilarity distance matrix, 4. Semi-structured interview using a tree diagram. Thus, both students and the expert introduced keywords relating to the space of the library. In addition, the expert perceived the library from the library management side, whereas the students had a user-centered perception.